The global warming survival handbook 77 essential skills to stop climate change--or live through it - Rothschild, David de (Melcher Media, 2007)
Describes ways to prevent global warming, including screwing in the right light bulb, choosing the right grocery bag, and eating vegetables, and includes ten humorous ways to survive on an overheated planet, including buying a camel.